Omics-Based Approach Reveals Complement-Mediated Inflammation in Chronic Lymphocytic Inflammation With Pontine Perivascular Enhancement Responsive to Steroids (CLIPPERS) - Blaabjerg, Morten; Hemdrup, Anne Louise; Drici, Lylia; Ruprecht, Klemens; Garred, Peter; Höftberger, Romana; Kristensen, Bjarne W.; Kondziella, Daniel; Sejbaek, Tobias; Hansen, Soren W.; Nielsen, Helle H.; Jensen, Pia; et al. (Frontiers in Immunology, 2018)
Objective: Chronic Lymphocytic Inflammation with Pontine Perivascular Enhancement Responsive to Steroids (CLIPPERS) is a rare syndrome with relapsing brainstem/cerebellar symptoms. To examine the pathogenic processes and investigate potential biomarkers, we analyzed combined materials of brain and CSF by comprehensive methodologies. Materials and Methods: To identify major pathways of perivascular inflammation in CLIPPERS, we first compared the CSF proteome (n=5) to a neurodegenerative condition, Alzheimer’s disease (AD, n=5). Activation of complement was confirmed by immunohistochemistry on CLIPPERS brain samples (n=3) and by ELISA in the CSF. For potential biomarkers, we used biomarker arrays, and compared inflammatory and vessel-associated proteins in the CSF of CLIPPERS (n=5) with another inflammatory relapsing CNS disease, multiple sclerosis (RMS, n=9) and healthy controls (HS, n=7). Results: Two hundred and seven proteins in the CSF discriminated CLIPPERS from AD. The complement cascade, immunoglobulins, and matrix proteins were among the most frequently represented pathways. Pathway analysis of upstream regulators suggested the importance of vascular cell adhesion protein 1 (VCAM1), IFN-, IL-1 and IL-10. Differential regulation of more than 10 complement proteins of the three complement pathways in the CSF pointed to the role of complement activation. Immunohistochemistry on brain samples confirmed the perivascular complement activation i.e. deposition of C3bc, C3d and the terminal C5b-9 complement complex that partially overlapped with accumulation of IgG in the vessel wall. Besides endothelial cell damage, reactivity to smooth muscle actin was lost in the walls of inflamed vessels, but the glia limitans was preserved. The semi-quantitative array indicated that increased level of IL-8/CXCL8 (P<0.05), eotaxin/CCL11 (P<0.01), and granulocyte-colony stimulating factor (P<0.05) in CSF could distinguish CLIPPERS from HS. The quantitative array confirmed elevated concentration of IL-8/CXCL8 and eotaxin/CCL11 compared to HS (P<0.05, respectively) besides increased levels of ICAM-1 (P<0.05) and VCAM-1 (P<0.001). The increased concentration of VCAM-1 were able to differentiate CLIPPERS from RMS (P<0.01), and a trend of elevated levels of ICAM-1 and IL-8/CXCL8 compared to RMS was also observed (P=0.06, respectively). Conclusions: Complement activation, IgG deposition, and alterations of the extracellular matrix may contribute to inflammation in CLIPPERS. VCAM1, ICAM1 and IL-8 in the CSF may differentiate CLIPPERS from RMS.